Effect of adding platelet-rich plasma to fat grafts in myringoplasty - Tamer Fawzy; Mohamed Hussein; Said Eid; Sherif Guindi (The Egyptian Journal of Otolaryngology, 2018)
Abstract Background Platelet-rich plasma (PRP) is an autologous product derived from whole blood through the process of gradient density centrifugation. Autologous PRP, with growth factors up to 8 times that of normal serum, has been shown to be safe and effective in promoting natural processes of wound healing. Our study aims to examine the effect of combining the fat graft with PRP in myringoplasty procedures indicated for TMP secondary to chronic suppurative otitis media (CSOM) and whether it can significantly promotes Tympanic membrane (TM) healing. Methods This prospective study included forty patients, presenting with dry tympanic membrane secondary to tubo-tympanic CSOM. Half the patients underwent fat graft Myringoplasty with PRP application (group A), while others served as control and received the fat graft only, without PRP (group B). Results In group A, eighteen cases (90%) significantly showed an intact tympanic membrane, while Eleven cases (55%) were successful in group B. P=0.044. Conclusion Topical autologous PRP application during fat plug Myringoplasty is highly successful with no reported postoperative infections and minimal morbidity.